(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the ethical and legal aspects of dictionaries and language change, focusing on the responsibility of lexicographers in documenting evolving language while considering the broader societal impacts. It examines the ethical concerns of inclusivity, representation, and sensitivity to social change, as well as the challenges posed by offensive or outdated language. The article also addresses legal issues, including copyright, trademark law, defamation, and the balance between free speech and censorship. Ultimately, it highlights the role of dictionaries in reflecting and shaping language, emphasizing the delicate balance between accurately documenting language and promoting socially responsible language choices.